Elevated polar ejection forces stabilize kinetochore-microtubule attachments. - Cane, S.; Ye, A.A.; Luks-Morgan, S.J.; Maresca, T.J. (Journal of Cell Biology, 2013)
Chromosome biorientation promotes congression and generates tension that stabilizes kinetochore-microtubule (kt-MT) interactions. Forces produced by molecular motors also contribute to chromosome alignment, but their impact on kt-MT attachment stability is unclear. A critical force that acts on chromosomes is the kinesin-10-dependent polar ejection force (PEF). PEFs are proposed to facilitate congression by pushing chromosomes away from spindle poles, although knowledge of the molecular mechanisms underpinning PEF generation is incomplete. Here, we describe a live-cell PEF assay in which tension was applied to chromosomes by manipulating levels of the chromokinesin NOD (no distributive disjunction; Drosophila melanogaster kinesin-10). NOD stabilized syntelic kt-MT attachments in a dose- and motor-dependent manner by overwhelming the ability of Aurora B to mediate error correction. NOD-coated chromatin stretched away from the pole via lateral and end-on interactions with microtubules, and NOD chimeras with either plus end-directed motility or tip-tracking activity produced PEFs. Thus, kt-MT attachment stability is modulated by PEFs, which can be generated by distinct force-producing interactions between chromosomes and dynamic spindle microtubules.